Motivasi, Kepemimpinan dan Stres Kerja Sebagai Faktor Determinan Terhadap Kinerja dengan Kepuasan Kerja Sebagai Variabel Intervening - Irma Normalia; Kartawan Kartawan; Yusuf Abdullah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to examine the influence of motivation, leadership and work stress as determinant factors on performance with job satisfaction as an intervening variable. The study was conducted on District employees in Tasikmalaya City. Sampling was carried out using the proportional stratified random sampling technique, with a total sample size of 152 samples, spread across 10 sub-district employees in Tasikmalaya City. The research instrument used was a questionnaire with a Likert scale. The analysis technique used structural equation modeling with the smartPLS application. The results of this research show that 1) Motivation, leadership, work stress, job satisfaction and performance of sub-district employees in Tasikmalaya City are in very good condition; 2) Motivation, leadership and work stress have a positive and significant effect on job satisfaction; 3) Motivation, leadership and work stress have a positive and significant effect on performance; 4) Motivation, leadership and work stress influence performance through job satisfaction as an intervening variable for subdistrict employees in Tasikmalaya City.